Hypoxia-inducible factor: role in cell survival in superoxide dismutase overexpressing mice after neonatal hypoxia-ischemia - Ga Won Jeon; R. Ann Sheldon; Donna M Ferriero (Korean Pediatric Society, 2019)
Background Sixty percent of infants with severe neonatal hypoxic-ischemic encephalopathy die, while most survivors have permanent disabilities. Treatment for neonatal hypoxic-ischemic encephalopathy is limited to therapeutic hypothermia, but it does not offer complete protection. Here, we investigated whether hypoxia-inducible factor (HIF) promotes cell survival and suggested neuroprotective strategies. Purpose HIF-1α deficient mice have increased brain injury after neonatal hypoxia-ischemia (HI), and the role of HIF-2α in HI is not well characterized. Copper-zinc superoxide dismutase (SOD)1 overexpression is not beneficial in neonatal HI. The expression of HIF-1α and HIF-2α was measured in SOD1 overexpressing mice and compared to wild-type littermates to see if alteration in expression explains this lack of benefit. Methods On postnatal day 9, C57Bl/6 mice were subjected to HI, and protein expression was measured by western blotting in the ipsilateral cortex of wild-type and SOD1 overexpressing mice to quantify HIF-1α and HIF-2α. Spectrin expression was also measured to characterize the mechanism of cell death. Results HIF-1α protein expression did not significantly change after HI injury in the SOD1 overexpressing or wild-type mouse cortex. However, HIF-2α protein expression increased 30 minutes after HI injury in the wild-type and SOD1 overexpressing mouse cortex and decreased to baseline value at 24 hours after HI injury. Spectrin 145/150 expression did not significantly change after HI injury in the SOD1 overexpressing or wild-type mouse cortex. However, spectrin 120 expression increased in both wild-type and SOD1 overexpressing mouse at 4 hours after HI, which decreased by 24 hours, indicating a greater role of apoptotic cell death. Conclusion HIF-1α and HIF-2α may promote cell survival in neonatal HI in a cell-specific and regional fashion. Our findings suggest that early HIF-2α upregulation precedes apoptotic cell death and limits necrotic cell death. However, the influence of SOD was not clarified; it remains an intriguing factor in neonatal HI.